POLICY STUDY: 'RAILMADAD' GRIEVANCE REDRESSAL MECHANISM FOR BETTER SERVICES TO RAIL PASSENGERS (International Journal of Food and Nutritional Sciences, 2022)
Indian Railways have been the life-line of the nation and over the period of time the Railways have been emerging as a better service provider. Indian Railways have implemented many reforms for providing not only better commuting or transportation service but as a holistic service sector in travel & tours, lodging & boarding as well. Development of such services have raised the bar and to be in better competition the Railways have been working on improvement of the safety & security as well as better amenities and services by resolving or addressing the problems faced by customers or passengers. The paper reflects upon the existing grievance redressal mechanism systems presently available with the Indian Railways for better services to its railway passengers.